Antithrombotic effect of Z4A5 on coronary thrombosis in a canine model of acute unstable angina. (27th May 2013) - Jing, Bo‐Bin; Li, Ying‐Xue; Zhang, Hui; Ren, Shu‐Ting; Wang, Mei; Li, Yi‐Ping; Shen, Xin‐Liang; Wang, Yi‐Li; Zang, Wei‐Jin; Wang, Bing
<x xml:space="preserve">Abstract</x> Background and Purpose The glycoprotein IIb/IIIa receptor is the final common pathway of platelet aggregation, regardless of the agonist, and thus represents an ideal therapeutic target for blocking coronary thrombosis. In this study, the anti‐platelet and antithrombotic actions of Z4A5, a new glycoprotein IIb/IIIa receptor inhibitor, were evaluated in a canine model of acute unstable angina. Experimental Approach Z4A5 was given i.v. as a bolus followed by 60 min of continuous infusion at doses of 30 μg·kg−1 + 1 μg·kg−1·min−1, 30 μg·kg−1 + 5 μg·kg−1·min−1 or 300 μg·kg−1 + 5 μg·kg−1·min−1. Its antithrombotic effect was evaluated in a model of coronary thrombosis, the injured, stenosed left circumflex coronary artery, in which platelet‐dependent cyclic flow reductions (CFRs) were induced by vascular compression and constriction to simulate clinical acute unstable angina. Platelet aggregation and coagulation parameters were determined in platelet‐rich plasma and platelet poor plasma respectively. Key Results The Z4A5 infusion induced a dose‐dependent reduction in CFR frequency, which returned to baseline levels after the termination of the infusion at low doses. At medium dose that inhibited most part of platelet aggregation, it increased tongue bleeding time marginally with no dramatic changes in haemodynamic and coagulation parameters. Furthermore, the inhibition of ADP‐induced platelet aggregation and prolonged bleeding time observed during Z4A5 infusion reverted to baseline levels after the termination of the infusion. Conclusions and Implications Z4A5 is an effective antithrombotic agent for coronary artery thrombosis with a rapid‐on and rapid‐off pharmacological profile, and could be used as an alternative treatment of coronary artery ischaemic syndromes.